Characterization of compatibilized blends of nylon 66/poly(2, 6-dimethyl-1, 4-phenylene ether)/high-impact polystyrene filled with phosphinate-based flame retardants: Mechanical property, rheological behavior, and flame retardancy. (September 2015) - Kim, Do Kyun; Song, Kwang Ho; Koo, Chong Min; Hong, Soon Man; Chae, Dong Wook
The optimum weight ratio of each component in the compatibilized blends of nylon 66/poly(2, 6-dimethyl-1, 4-phenylene ether)/high-impact polystyrene with polystyrene-co-maleic anhydride and styrene–ethylene–butylene–styrene block copolymer grafted with maleic anhydride was determined in terms of exhibiting balanced mechanical properties. The mechanical strength of the blends was deteriorated with increasing phosphinate-based flame retardant content while the tensile modulus increased. For UL94V test, the addition of ∼10 wt% phosphinate did not have a significant effect on the flame retardancy showing V2 grade while further addition gave rise to char formation resulting in V0 grade. Limiting oxygen index values increased greatly by ca. 34% at 5 wt% phosphinate, followed by mild increase by further addition. Heat release rate peaks of the blends were reduced and broadened with increasing phosphinate content showing little difference from 15 wt%. The complex viscosity increased with phosphinate content, but its increasing extent decreased at a high frequency. In the Cole–Cole plot, the presence of the phosphinate shifted the plot from unfilled blends without showing a single master curve depending on its loading level.